Quantifying epithelial cell proliferation on curved surfaces - Chang, Ya-Wen; Cruz-Acuña, Ricardo; Tennenbaum, Michael; Fragkopoulos, Alexandros A.; García, Andrés J.; Fernández-Nieves, Alberto (Frontiers in Physics, 2022)
Out-of-plane curvature is an important, but poorly explored geometric parameter that influences cell behavior. We address the impact of curvature on epithelial proliferation through monitoring how MDCK cells proliferate on planar and curved toroidal hydrogel substrates with a broad range of Gaussian curvatures. We illustrate in detail the imaging processing methodology to characterize curved surfaces and quantify proliferation of cells. We find that MDCK cells grow readily on both curved and flat surfaces and can cover the entire surface of the toroidal structure as long as the initial seeding is uniform. Our analysis shows that proliferation does not depend on Gaussian curvature within the range probed in our experiment, but rather on cell density. Despite epithelial proliferation is insensitive to the curvature range presented in this study, the toroidal-construct fabrication technique and image processing methodology may find utility for probing cell processes like collective migration, as it involves long-range force transmission.